Complete chloroplast genome sequence and annotation of Machilus salicina Hance, 1885 (lauraceae). Issue 5 (4th May 2022) - Xiaoxuan, Long; Shi, Wenbo; Song, Weicai; Han, Weiqi; Yang, Guiwen; Wang, Shuo
Abstract: Machilus salicina Hance, 1885 is a species of flowering plant in the family Lauraceae and is mainly found at low altitudes in southern China. In this study, we assembled and annotated the complete chloroplast genome of M. salicina for the first time. We analyzed the general features of M. salicina and constructed a phylogenetic tree based on 15 Lauraceae species. The chloroplast genome of M. salicina had a total length of 153, 943 bp. The length of a large single copy region, a small single copy region, and two inverted repeat regions were 93, 689 bp, 20, 070 bp, and 20, 092bp, respectively. A total of 128 genes were detected, which included 84 protein-coding genes, 36 tRNAs and 8 rRNAs. The GC content of M. salicina complete chloroplast genome was 39.1%. The phylogenetic tree indicated that M. salicina was closely related to M. yunnanensis .